Assessment of Suitability of Tree Species for Bioenergy Production on Burned and Degraded Peatlands in Central Kalimantan, Indonesia - Maimunah, S.; Rahman, S.A.; Samsudin, Y.B.; Artati, Y.; Simamora, T.I.; Andini, S.; Lee, S.M.; Baral, H. (MDPI, 2018)
Large areas of deforested and degraded land, particularly degraded peatlands, need a viable long-term solution for restoration, ideally one that ensures energy security without compromising food security or biodiversity conversation. To address a knowledge gap on the most adaptive bioenergy crop(s) for degraded lands, this research project assessed the survival and growth performance of potential bioenergy crops to restore burned and degraded peatlands. Our methodology compared the bioenergy species with the potential to survive in extreme environments, i.e., gamal [Gliricidia sepium (Jacq.) Walp.], kaliandra (Calliandra calothyrsus Meissner), kemiri sunan [Reutealis trisperma (Blanco) Airy Shaw], and nyamplung (Calophyllum inophyllum L.). Observed parameters are plant survival rates, tree height, and circular stem growth. The experiment was conducted between March 2016 to February 2017 in a two-hectare demonstration plot on burned and degraded peatland in Buntoi village, Pulang Pisau, Central Kalimantan province. Using a split plot design, two treatments were given to each species, i.e., monoculture plantation and agroforestry (intercropped with Ananas comosus (L.) Merr.); with each treatment, the species were replicated on two separate plots. Results indicate that nyamplung is the most adoptable species followed by kemiri sunan, however both species performed very well under agroforestry treatment when compared with monoculture. Further study is needed to assess the productivity and associate biofuel yield.